Apparent diffusion coefficients in prostate cancer: correlation with molecular markers Ki‐67, HIF‐1α and VEGF. (9th January 2018) - Ma, Teng; Yang, Shaolin; Jing, Haiyan; Cong, Lin; Cao, Zhixin; Liu, Zhiling; Huang, Zhaoqin
Abstract : Prostate cancer (PCa) is the second most common cancer in men. The Gleason score (GS) and biomarkers play important roles in the diagnosis and treatment of patients with PCa. The purpose of this study was to investigate the relationship between the apparent diffusion coefficient (ADC) and the molecular markers Ki‐67, hypoxia‐inducible factor‐1α (HIF‐1α) and vascular endothelial growth factor (VEGF) in PCa. Thirty‐nine patients with 39 lesions, who had been diagnosed with PCa, were enrolled in this study. All patients underwent diffusion‐weighted magnetic resonance imaging (DW‐MRI) ( b = 800 s/mm 2 ). The expression of Ki‐67, HIF‐1α and VEGF was assessed by immunohistochemistry. Statistical analysis was applied to analyze the association between ADC and prostate‐specific antigen (PSA), GS and the expression of Ki‐67, HIF‐1α and VEGF. The group differences in ADC among different grades of Ki‐67, HIF‐1α and VEGF were also analyzed. The mean ± standard deviation of ADC was (0.76 ± 0.27) × 10 −3  mm 2 /s. ADC correlated negatively with PSA and GS ( p < 0.05). The Ki‐67 staining index (SI), HIF‐1α expression and VEGF expression in PCa were correlated inversely with ADC, controlling for age ( r = –0.332, p < 0.05; r = −0.662, p < 0.0005; and r = −0.714, p < 0.0005, respectively). ADC showed a significant difference among different grades of Ki‐67 ( F = 9.164, p = 0.005), HIF‐1α ( F = 40.333, p < 0.0005) and VEGF ( F = 22.048, p < 0.0005). In conclusion, ADC was correlated with PSA, GS, and Ki‐67, HIF‐1α and VEGF expression in patients with PCa. ADC may be used to evaluate tumor proliferation, hypoxia and angiogenesis in PCa. Abstract : The apparent diffusion coefficient (ADC) was correlated with prostate‐specific antigen (PSA), Gleason score (GS), and Ki‐67, hypoxia‐inducible factor‐1α (HIF‐1α) and vascular endothelial growth factor (VEGF) expression in patients with prostate cancer (PCa). These findings suggest that ADC may be used as an imaging biomarker to evaluate tumor proliferation, hypoxia and angiogenesis in PCa.